Explaining cybercrime victimization using a longitudinal population-based survey experiment. Are personal characteristics, online routine activities, and actual self-protective online behavior related to future cybercrime victimization? - van ’t Hoff-de Goede, M.S. (Journal of crime and justice, 2024)
With the increasing prevalence of cybercrime victimization there is a growing need for prevention. Previous studies have attempted to uncover risk factors associated with cybercrime victimization in the areas of personal characteristics and online routine activities. This article aims to take the field a step further by including actual self-protective online behavior, obtained through a population-based survey experiment (N = 1886), as a risk factor for cybercrime victimization. In wave 1 of our longitudinal design, personal characteristics, online routine activities, and actual self-protective online behavior concerning password strength, clicking behavior, sharing personal information, and handling phishing emails were measured. In wave 2, cybercrime victimization of several types of cyber-enabled and cyber-dependent cybercrimes was measured one year later. Results indicate that few personal characteristics, online routine activities, and self-protective online behaviors are related to the odds of becoming a cybercrime victim. This furthermore illustrates the heterogeneity of cybercrime victimization, since most significant factors only seem to be related to the risk of one particular type of cybercrime. These results indicate that to explain cybercrime victimization, the research field needs to shift its focus and adapt to new online developments.